Méthodes et contenus des premières réunions du groupe FUORI ! de Milan : une histoire palpitante et violente - Corrado Levi (Genre, Sexualité et Société)
This article was published in two different numbers of the review "FUORI!": the first part "Methods and Contents of the Group FUORI! of Milan’s first meetings" in the N°3, in September 1972, the second "A Thrilling and Violent Story" in N°8, in March 1973. Corrado Levi, militant in the Italian homosexual revolutionary movement from its start, gives us in this text a good idea of the consciousness-raising work realized by the militant homosexual groups, inspired by the women's movements. "Liberation" comes first and foremost by a liberation of speech and is before all a liberation of one-self. Confronting the other, which has its foundations in one's own homosexual experience, is the starting point towards a reflection that escapes traditional political views. The "politics of experience" are thus to be understood as a day-to-day effort of consciousness-raising and of one's self-construction based on one's encounter with the collective and, above all, stemming from the experience that one's body makes of the ideological and economical domination. The discovery of the regions of one's body inhibited as of yet and the possible boundaries that libertarian practices permit to transcend and to broaden compose the object itself of this research that, in the same way the laboratories of political experimentation did, the groups of revolutionary homosexuals devoted themselves to explore.